Development of Bighead Catfish (Clarias macrocephalus) Culture for Sustainable Aquaculture in Cambodia Workshop report - Amran, Aaqillah; Ahmad Fatan, Nurulhuda; Abu Bakar, Khairul Rizal; Chin, Hooi Bing; Ramli, Muhammad Rahimi; Sharbini, Ning; Sok, Sao; Sonoan, Kri; Soth, Vithun; Sithirith, Mak; Reyes, Manuel; Hok, Lyda; et al. (WorldFish, 2023)
The purpose of the Workshop on Development of Bighead Catfish (Clarias macrocephalus) Culture for Sustainable Aquaculture in Cambodia was to share ongoing research on bighead catfish (BC) in Cambodia and discuss the next possible steps with all the participants, building on current activities and opportunities available in the country.